RETRACTED: Strategic solutions for sustainable environmental waste management - Hudayberganov Dilshod; Jumaeva Zulfiya; Abdullaeva Zulfiya; Matmuratova Nigora; Ozodova Farida; Farxodova Sharifa (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001